PENGARUH WEBSITE DESIGN E-COMMERCE HOME PRODUCT TERHADAP CUSTOMER SATISFACTION DI INDONESIA - Damayanti, Shofia; Widjaja, Fitri Novika; Tedjakusuma, Adi Prasetyo (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
The rapid growth of E-commerce in Indonesia has changed consumer shopping habits, particularly for household products. E-commerce offers the convenience of shopping without visiting offline stores. However, the research on the impact of e-commerce website design on customer satisfaction in the household product sector remains limited. This study aims to analyze the effects of website design, information quality, security, responsiveness, and trust on customer satisfaction. A quantitative approach is used, involving 374 respondents who have purchased household products online in the past six months in platforms like IKEA, Ace Hardware, or Informa. The data was collected via Google Forms and was analyzed using Structural Equation Modeling (SEM) with Smart PLS 4 software. The results indicate that website design, information quality, responsiveness, and trust significantly impact customer satisfaction, while security does not. Based on these findings, E-commerce companies in Indonesia are advised to improve website design, enhance information quality, and offer responsive customer service to boost customer satisfaction